Innovative 3D-printed porous TC4 prosthesis with nano-thin tantalum coating for treating complex wrist bone defects: A preliminary report of 3 cases - Chang Chen; Huaquan Fan; Ge Chen; Zhong Li; Puquan Wang; Fuyou Wang (Journal of Orthopaedic Surgery)
Background: Bone defects pose a significant orthopedic challenge, impacting millions of patients worldwide annually. In our prior research, we innovatively applied magnetron sputtering (MSP) technology to prepare nano thin amorphous tantalum (Ta) coatings on titanium alloy (Ti - 6Al - 4V, TC4) substrate, achieving exceptional interfacial adhesion, comprehensive coverage, and notable biological attributes. The purpose of this study is to investigate the clinical outcomes of TC4-based Ta-coated implants in addressing wrist bone defects, thereby offering valuable insights for future clinical applications. Methods: A prospective observational study was conducted from October 2023 to December 2024 to assess the clinical efficacy of TC4-based Ta-coated implants. Three patients, comprising two males and one females, were included and underwent personalized prosthesis design and surgical implantation in accordance with established protocols. Postoperative assessments were conducted utilizing the Visual Analogue Scale (VAS), and Cooney modification of the Green and O’Brien score to gauge the patients’ symptomatic relief and functional recovery. Additionally, regular imaging follow-ups were implemented to monitor the progress and outcomes. Results: All three patients underwent surgery successfully. As of the latest follow-up, all patients exhibited significant improvements in pain symptoms (assessed using VAS scores) and functional outcomes. No patients experienced serious complications such as infection, prosthesis loosening, or vascular and nerve damage. Conclusion: This study confirmed the clinical efficacy of customized TC4-based Ta-coated implants in the treatment of wrist bone defects. The nanoscale Ta coating significantly enhances the bone integration ability, thereby effectively improving clinical outcomes. This innovative approach not only demonstrates the potential to overcome the inherent drawbacks of conventional titanium alloys and pure Ta but also offers a highly prospective solution for the treatment of complex wrist bone defects. Future research should be directed towards enhancing manufacturing processes and undertaking more extensive clinical trials for providing evidence-based guidance for clinical applications.